The Effect of Compensation and Work Discipline on Work Productivity through Job Satisfaction - Samsuri; Lia Kian; Palahudin (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
The tea plantation industry in Indonesia faces ongoing challenges in sustaining employee productivity due to cost pressures, competitive demands, and difficulties in implementing effective human resource management practices, where the combined effects of compensation and work discipline, particularly mediated by job satisfaction, remain underexplored. This study aims to examine the direct and indirect influences of compensation and work discipline on work productivity, with job satisfaction serving as an intervening variable, among employees. The research adopted a quantitative approach using path analysis. Data were collected from 100 purposively selected employees through questionnaires measured on a five-point Likert scale. Analysis was conducted with statistical software to test direct effects, indirect effects via the Sobel test, and total effects. The results indicate that compensation and work discipline significantly and positively affect job satisfaction, with compensation showing a stronger influence. Both variables also directly enhance work productivity, again with compensation exerting a greater impact. Job satisfaction partially mediates these relationships, contributing meaningful indirect effects. Compensation demonstrates a substantially larger total effect on work productivity compared to work discipline, highlighting the need for management to prioritize competitive compensation and disciplined work practices to boost employee productivity.